Fitness industry in Spain; analysis of low-cost and whole body electromyostimulation centers - de la Cámara Serrano, M. A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2015)
The evolution of the fitness sector is a constant that has been repeating itself for years. New trends and business models are emerging in order to gain a foothold in the sector or attached on it. Low-cost gyms and whole body electromyostimulation centers currently present significant growth in Spain. The aim of this study is to analyze this type of centers and reasoning the possible impact that they may have on the fitness sector. In both cases, the growth and expansion of these centers has turned out to be fast and constant, and it is expected to be continued like that during the next year. The increase presence of these centers has an impact both in the rest of companies of the sector an in the final user. Different points and observed factors may influence the consolidation, permanence an stability of both centers.